DEVELOPING STUDENTS' CULTURAL SKILLS USING ENGLISH FAIRY TALES (Emergent: Journal of Educational Discoveries and Lifelong Learning (EJEDL), 2025)
This article discusses the use of English fairy tales in fostering students' cultural skills. It is an effective method that not only develops language abilities but also introduces children to the cultural values of English-speaking countries.